A mini-review on the use of waste in the production of sustainable Portland cement composites - Hansted, Felipe Augusto Santiago [UNESP]; Mantegazini, Diunay Zuliani [UNESP]; Ribeiro, Thais Marchetti [UNESP]; Gonçalves, Carlos Eduardo Cardoso [UNESP]; Balestieri, Jose Antonio Perrella [UNESP] (SAGE Publications, 2023)
With an increase in climate and environmental issues awareness, the use of waste of various types has gained increased visibility, acknowledging that wastes are any and all kinds of unused materials from the production process or after using the final product for its intended purpose. The use of wastes to produce alternative cement materials is an alternative to reduce the use of natural resources. Forestry residues, ash, plastic residues, LDPE/Al composites, and geopolymer materials are some of the possible residues used for the partial replacement of cement materials. The objective of this research is to establish how these materials relate to each other, based on a topic review and how they can contribute towards sustainability. The study was performed on several scientific article search engines, in which the keywords ‘Carton Packages’, ‘Wood Waste’ and ‘Geopolymers’ were inserted, and then a refinement was carried out using the term ‘Cement Materials’. Such analysis allowed the generation of information related to publication numbers, countries, research areas, as well as publication types. Co-authorship networks of organization, co-citation of references, co-occurrence of keywords, among others, were also plotted. Through this bibliometric analysis, it was possible to reveal the structure of the research, analyse the developments and predict the future directions for the research regarding the use of residues in the production of sustainable Portland cement composites.
Keywords: Carton packages; cement materials; geopolymers; sustainability; wood waste